Red hot lies how global warming alarmists use threats, fraud, and deception to keep you misinformed - Horner, Christopher C. (Regnery Pub., 2008)
In Red Hot Lies, bestselling author Christopher Horner--himself the target of Greenpeace dirty tricks and alarmist smears--exposes the dark underbelly of the environmental movement: from power-hungry politicians blacklisting scientists who reject global warming alarmism to mainstream media outlets that openly reject the notion of "balance.".